Assessments of science from scientific practice - Orozco, Richard Antonio (2012)
In this article, the author shows how an idealized interpretation of science has led common sense to imagine a supposed ethical neutrality of it. And even, it has been assumed that science should be the guide of the society but without assuming any dependency of the latter to the former. The author then shows a new way of interpreting science from scientific practices, a model recently made since the 1960s in the post-Kuhnian philosophy of science. In this adaptive andpragmatist model, science reveals its greater dependence on social values and so we can speak of an axiology extended for science